2020
DOI: 10.1101/2020.06.21.163303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A general role for ventral white matter pathways in morphological processing: going beyond reading

Abstract: The ability to recognize the structural components of words, known as morphological processing, was recently associated with the bilateral ventral white matter pathways, across different writing systems. However, it remains unclear whether these associations are specific to the context of reading. To shed light on this question, in the current study we investigated whether the ventral pathways are associated with morphological processing in an oral word production task that does not involve reading. Forty-five… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 131 publications
2
5
0
Order By: Relevance
“…Our high subject-level robustness results (Figs. 4C, 5C, 6C) dovetail with the results of a recently published study that used tractometry in a sample of 45 participants (51) and found high subject-level correlations between the mean tract values of FA and MD for two different pipelines: deterministic tractography using the diffusion tensor model (DTI) as the ODF model (essentially identical to a pipeline used in our supplementary analysis, described in "DTI Configuration") and probabilistic tractography using CSD as the ODF model. Consistent with our results on the HCP-TR dataset, slightly higher subject robustness was found for MD than for FA.…”
Section: Subject Robustness Remains High Despite Differences In the Spatial Extent Of Bundlessupporting
confidence: 79%
“…Our high subject-level robustness results (Figs. 4C, 5C, 6C) dovetail with the results of a recently published study that used tractometry in a sample of 45 participants (51) and found high subject-level correlations between the mean tract values of FA and MD for two different pipelines: deterministic tractography using the diffusion tensor model (DTI) as the ODF model (essentially identical to a pipeline used in our supplementary analysis, described in "DTI Configuration") and probabilistic tractography using CSD as the ODF model. Consistent with our results on the HCP-TR dataset, slightly higher subject robustness was found for MD than for FA.…”
Section: Subject Robustness Remains High Despite Differences In the Spatial Extent Of Bundlessupporting
confidence: 79%
“…It is worth mentioning that FAT is often implicated in verbal fluency tasks along with other tracts, especially IFOF, although the evidence is, as in the other cases, far from convergent. Some studies have reported a correlation with both category and letter fluency scores (Blecher et al, 2019;Costentin et al, 2019;Li et al, 2017;Sanvito et al, 2020), some only with letter/phoneme fluency (Cipolotti et al, 2016;Keser et al, 2020), some with morpheme-based fluency (Yablonski et al, 2021) and some with none of these (Tseng et al, 2019;Vallesi & Babcock, 2020). Costentin et al (2019) found a correlation between verbal fluency scores and lesions to FAT and a number of other tracts in 48 individuals with Parkinson's Disease.…”
Section: Frontal Aslant Tract (Fat)mentioning
confidence: 98%
“…Forty-five neurotypical adults (29 females; mean age 26.45 ± 3.72 years; Table 1) were recruited for this study. All the analyses reported here are completely new, but some data from this sample has been reported as part of a research project focusing on associations between well-known language pathways and word structure (Yablonski et al, 2021;. All participants were right handed as estimated by the Edinburgh handedness inventory (Oldfield, 1971; Table 1), and had no history of a diagnosed speech impairment, learning disability, or neurological condition.…”
Section: Participantsmentioning
confidence: 99%
“…We also calculated a standardized verbal fluency score based on age-appropriate Hebrew norms (Kavé & Knafo-Noam, 2015). The analysis of standardized verbal fluency scores in the current sample is reported in a previous paper (Yablonski et al, 2021). Note, however, that this previous paper did not examine the associations between verbal fluency measures and the CPs, which is the focus of the current study.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation